ANALISIS KEPUTUSAN PETANI BERUSAHATANI NILAM DI KECAMATAN POLINGGONA KABUPATEN KOLAKA - Helviani Helviani; Masitah Masitah; Aan Wilhan Juliatmaja; Suci Ramadani (AGRIBIOS, 2023)
Patchouli is one of the primary essential oil-producing plants in Indonesia. The oil produced by the patchouli plant is called patchouli oil (patchouli oil), which is used as a raw material in perfume, cosmetics and other industries. In Indonesia, there are several patchouli oil production centres. One is in Polinggona District, Kolaka Regency, Southeast Sulawesi Province. To start farming activity, some factors influence farmers in making the farmer's decision to carry out patchouli farming. Decision-making is a process of selecting the best alternative from various alternatives systematically to be followed up as a way to solve problems that occur. This research aims to determine what factors influence farmers' decisions to carry out value farming in Polinggona District, Kolaka Regency. This research method uses a quantitative descriptive method with the help of multiple linear regression data analysis tools. The research sample was determined using the Slovin method. The results of this research state that the land area variable has the most significant influence on farmers' decisions in patchouli farming because it has a calculated t value that is greater than the education variable and the income variable.